2020
DOI: 10.3390/su12145815
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Salinity on the Removal of Ni and Zn by Sorption onto Iron Oxide- and Manganese Oxide-Coated Sand

Abstract: The influence of salinity on the single and binary sorption of Ni and Zn onto iron oxide- and manganese oxide-coated sand (IOCS and MOCS) was investigated at pH = 5. The single sorption experimental data were fitted to Freundlich, Langmuir, Dubinin–Radushkevich, and Sips models, and a nonlinear sorption isotherm was observed (NF = 0.309–0.567). The higher Brunauer–Emmett–Teller (BET) surface area (ABET) and cation exchange capacity (CEC) of MOCS contributed to the higher maximum sorption capacities (qmL) of Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
3
4
1
Order By: Relevance
“…This is consistent with the results of Choi et al. (2020), where sorption of both Zn and Ni by a MOCS was decreased in the presence of the other, but Zn sorption was dominant. Similarly, Gou et al.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the results of Choi et al. (2020), where sorption of both Zn and Ni by a MOCS was decreased in the presence of the other, but Zn sorption was dominant. Similarly, Gou et al.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that Ni and Zn competed for sorption sites at the MOCS surface, and that Zn sorption was dominant. This is consistent with the results of Choi et al (2020), where sorption of both Zn and Ni by a MOCS was decreased in the presence of the other, but Zn sorption was dominant. Similarly, Gou et al (2018) reported that Zn sorption by an Al oxide was unaffected by the presence of Ni, whereas Ni sorption decreased in the presence of Zn.…”
Section: Sorption Kineticssupporting
confidence: 92%
See 1 more Smart Citation
“…Several literatures have reported similar results (adsorption capacities of Ni > that of Zn) for adsorbents such as Na-montmorillonite [18]. The adsorption affinity of Ni and Zn decreased with the increase salinity (30% ) owing to competition between the added metals and cations in background solution by the limited cation exchange sites [45][46][47]. Table 3 summarizes the comparison of Ni and Zn sorption capacities of Langmuir model for various adsorbents found in literature.…”
Section: Ni and Zn Adsorptionmentioning
confidence: 58%
“…The adsorption method has become preferred for removing heavy metals from wastewater because of its high effectiveness, simplicity and flexibility in plant design, operation and environmental considerations. Numerous adsorbents have been used to remove heavy metals such as activated carbon, alumina, zeolites, iron oxides and manganese oxide [23][24][25][26]; agricultural waste such as coffee grounds, walnut shells, sawdust and rice husk ash [27][28][29]; industrial waste such as fly ash or bottom ash from power plants, and red sludge and steel slag [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%